With a little help from my friends: ministerial alignment and public spending composition in parliamentary democracies. Issue 1 (1st January 2019) - Bojar, Abel
ABSTRACT: The determinants of public spending composition have been studied from three broad perspectives in the scholarly literature: functional economic pressures, institutional constraints and party-political determinants. This article engages with the third perspective by placing intra-governmental dynamics in the centre of the analysis. Building on the portfolio allocation approach in the coalition formation literature and the common pool perspective in public budgeting, I theorize that spending ministers with party-political backing from the prime minister or the finance minister are in a privileged position to obtain extra funding for their policy jurisdictions compared to their colleagues without such support or without any partisan affiliation (non-partisan ministers). Via a system of equations on six spending categories using seemingly unrelated regressions as well as Prais–Winsten panel regressions on a sample of 32 parliamentary democracies over two decades, I offer mixed evidence for the impact of party-political alignment. While the relative share of four of the six budget categories systematically increases under the party-political alignment of the prime minister, the impact of finance minister alignment is only significant for the economic budget.